2008
DOI: 10.1007/s00464-008-0199-z
|View full text |Cite
|
Sign up to set email alerts
|

Rescue ERCP and insertion of a small-caliber pancreatic stent to prevent the evolution of severe post-ERCP pancreatitis: a case-controlled series

Abstract: Rescue pancreatic stenting with small-caliber prophylactic pancreatic stents seems to be a safe and effective procedure that might be feasible to stop the evolution of severe post-ERCP pancreatitis, but prospective controlled studies are clearly demanded to support this innovative approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 18 publications
0
14
0
2
Order By: Relevance
“…5 Interestingly, a recent case series explored the role of rescue ERCP a few hours after the initial procedure to prevent post-ERCP pancreatitis. 25 Several pharmacological agents have also been investigated for the prevention of post-ERCP pancreatitis. The role of pharmacological agents in combination with pancreatic stents has not been adequately studied.…”
Section: Discussionmentioning
confidence: 99%
“…5 Interestingly, a recent case series explored the role of rescue ERCP a few hours after the initial procedure to prevent post-ERCP pancreatitis. 25 Several pharmacological agents have also been investigated for the prevention of post-ERCP pancreatitis. The role of pharmacological agents in combination with pancreatic stents has not been adequately studied.…”
Section: Discussionmentioning
confidence: 99%
“…Madácsy et al, in a case series, described the use of rescue pancreatic stenting to prevent the evolution of severe PEP. 33 Fejes et al reported that temporary pancreatic stenting can serve as a good bridging procedure in 27 patients with severe ABP in whom biliary EST was unsuccessful. 34 However, the number patients in the study was small, and the lack of a control group limited the full understanding of the consequences of failed stenting.…”
Section: Discussionmentioning
confidence: 99%
“…30,33 Furthermore, preliminary studies have suggested that "salvage" PSP may be beneficial early in the course of PEP for patients who did not originally receive a stent, or in the case of early stent dislodgement. 34,35 Additional studies including a control group are necessary to fully evaluate PSP for this indication.…”
Section: Prophylactic Pancreatic Stent Placementmentioning
confidence: 99%